TTW (Think-Talk-Write) Strategy; Does It Have an Effect on Students’ Writing Achievement at SMAN 4 Kendari? - Arista, Wisdar; Mursalim, Mursalim; Nurindah, Nurindah (Universitas Halu Oleo, 2021)
The objective of this study was to find out the effect of TTW (Think-Talk-Write) strategy on students’ writing achievement at SMAN 4 Kendari. This study used quasi-experimental design that consisted of experimental class and control class. The sample of this study were students at class X MIA2 and X MIAOlimpiade at SMAN 4 Kendari in academic years 2019/2020. The sample taken by using random sampling and the total numbers of students were 72, 36 for the experimental class (X MIA2) and 36 for the control class (X MIAOlimpiade). The instrument of the study was a writing test that focused on descriptive text. The writer collected the data by giving pre-test in both of the classes, giving treatment in experimental by giving TTW strategy and non-TTW strategy in control class, and giving post-test in both of the classes. In analyzing the data, the study used SPSS 16.0 version and independent sample t-test for hypothesis testing. The findings of this study showed that students’ mean score of post-test in the experimental class was 70.14. It was raised 10.31 points from its pre-test (59.86), while students’ mean score of post-test in control class was 65.5. It was only raised 6.21 points from its pre-test (59.29). Besides, the value of the degree of freedom (df)= 68, t=3.523, and sig (2 tailed)=0.001. It means that the probability (sig) value was lower than α (p-value < α or 0.001 < 0.05). Therefore, TTW strategy has a significant effect on students’ writing achievement at first-grade of SMAN 4 Kendari.